Artistic Formation Styles For Second Stage Students Productions in Arabic Handwriting ( Stylistic Study) - رشك خضير, حسين; كاظم محمد, جواد (Journal of College of Education, 2020)
The aim of the research is to reveal of artistic formation styles for the second stage students in the subject of Arabic Handwriting. The Researcher adopted analysis application form consists of (7 items) concluding each formation and its features, after made its design and showed it to the experts ; some holding modifications are completed to appear finally. After the researcher assured from its credibility and its fixation , he applied it on the sample of the research that counted 28 artistic production. These sample of the research was chosen by the researcher intentionally using the analysis according to the adopted application form for this purpose .The results appeared that the most of well-done artistic works for the second stage students in 2018- 2019 are one formation style (the horizontal style) in 95 % and in 5% in circular formation style. The causes of these results get back to the cognitive weakness level and there were no enough information about the others main artistic formation styles( level formation , polar formation , pyramidal formation and circular formation) for guaranteeing the variety and formation to achieve artistic gratefulness to the Arabic Handwriting ; to achieve that can be included in the syllabuses of the subject of the Arabic Handwriting. This subject has the principle of artistic formation of the Arabic Handwriting and its components that based on it and the formation styles as well that are the aim of the research.
Keywords: Artistic Formation Styles, Second Stage Students, Arabic Handwriting